New type of cave in the Tien Phuoc District, Quang Nam Province, Viet Nam - Nguyen, Giang Thi Truong; Xuan, Nam Nguyen; T, Hieu P.; Pham, Minh (Faculty of Geography, Universitas Gadjah Mada, 2025)
Cave systems in Vietnam typically develop in limestone terrains, which cover about 20% of the national territory and are concentrated mainly in the north. In contrast, Tien Phuoc District (Quang Nam Province) is located in central Vietnam, featuring a hilly topography composed primarily of metamorphic rocks, with no previously recorded limestone terrain. The recent discovery of